2002
DOI: 10.1271/bbb.66.1262
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Diversity in Lignan Biosynthesis ofArctium lappaL.

Abstract: The stereochemistry of lignan biosynthesis in Arctium lappa L. is regulated organ-specifically. (+)-Secoisolariciresinol [81% enantiomeric excess (e.e.)] was isolated from A. lappa petioles. In sharp contrast, lignans whose predominant enantiomers have the opposite absolute configuration to that of (+)-secoisolariciresinol [i.e., (-)-matairesinol (>99% e.e.), (-)-arctigenin (>99% e.e.), and (-)-secoisolariciresinol (65% e.e.)] were isolated from seeds of the species. The stereochemical diversity of secoisolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
(43 reference statements)
0
34
0
Order By: Relevance
“…β-Peltatin 6-O-methyltransferase was isolated and characterized from cell suspension cultures of Linum nodiflorum by Kranz and Petersen (Kranz and Petersen 2003). Members of the tribe Cynareae in the family Asteraceae such as Carthamus tinctorius (safflower) are enriched with 4′-O-methyldibenzylbutyrolactone lignans such as arctigenin and arctiin (Figure 2), especially in their seeds (Hänsel et al 1964;Nishibe et al 1972;Palter and Lundin 1970;Palter et al 1971;Palter et al 1972;Sakakibara et al 2007;Suzuki et al 2002b;Umezawa 2003b). Our survey of lignans in C. tinctorius indicated that matairesinol and arctigenin (or their glucosides) started to accumulate several days after flowering (DAF) ).…”
mentioning
confidence: 99%
“…β-Peltatin 6-O-methyltransferase was isolated and characterized from cell suspension cultures of Linum nodiflorum by Kranz and Petersen (Kranz and Petersen 2003). Members of the tribe Cynareae in the family Asteraceae such as Carthamus tinctorius (safflower) are enriched with 4′-O-methyldibenzylbutyrolactone lignans such as arctigenin and arctiin (Figure 2), especially in their seeds (Hänsel et al 1964;Nishibe et al 1972;Palter and Lundin 1970;Palter et al 1971;Palter et al 1972;Sakakibara et al 2007;Suzuki et al 2002b;Umezawa 2003b). Our survey of lignans in C. tinctorius indicated that matairesinol and arctigenin (or their glucosides) started to accumulate several days after flowering (DAF) ).…”
mentioning
confidence: 99%
“…1). Since the biosyntheses of lignans as an enantiomeric mixture have been reported, 6) optically pure synthesized lignans were used in this research. The lipoprotein-antioxidant activity of isolated 2 0 -hydroxy dihydroguaiaretic acid 7) and lipoxygenase inhibition of nordihydroguaiaretic acid (NDGA) have been reported.…”
mentioning
confidence: 99%
“…1,42.6,50.4,55.9,59.0,70.6,72.7,82.7,108.4,111.3,114.2,114.4,118.8,121.3,132.4,134.8,143.9,145.0,146.5,146.6;MS (EI) 7,43.2,48.8,55.87,55.89,58.6,72.3,73.1,82.1,109.0,111.2,113.9,114.3,119.2,121.3,131.6,132.0,143.9,144.6,146.1,146.4;MS (EI) 3,44.4,53.4,55.86,55.88,59.0,72.8,83.8,108.6,111.2,114.1,114.2,119.1,121.4,132.2,134.2,143.9,144.9,146.4,146.5;…”
Section: ■ Materials and Methodsmentioning
confidence: 99%